Can offshore balancing be a viable strategy for the United States in North-East Asia? - Lee, Benedict Kai Ming (Nanyang Technological University, 2020)
Given the debate over offshore balancing as an alternative strategy for the US, the purpose of this paper is to evaluate if offshore balancing can be a viable strategy for the US in North-East Asia by conducting a quantitative study on the military and latent power of China, Japan, South Korea and Russia. This paper argues that offshore balancing is a viable strategy for the US in North-East Asia since Japan and South Korea are capable of denying China air and sea control in the East China Sea in the short-term. However, offshore balancing may not be feasible in the long-term since Japan and South Korea are unable to balance against China’s defence spending, military modernisation and latent power over time. Moreover, there is an opportunity for the US to draw Russia away from the China-Russia alliance.